Evaluasi Layanan Tanggap Darurat Command Center 112 di Surabaya Tinjauan terhadap Badan Penanggulangan Bencana Daerah (BPBD) Kota Surabaya - Putra, Davin Bintang Dwi; Jaelani, Zafi Putra; Windayu, Giwang Sekar; Nanda, Anya Citra Kurnia (VISA: Journal of Vision and Ideas, 2024)
Command Center 112 is a unit that works to serve the community in emergencies. Evaluation has an important role in improving the quality of public services, therefore public service standards should not be ignored because this can reduce the quality of services offered to the public. The aim of this research is to identify challenges and problems faced in the emergency response service process and suggest improvements or solutions. The theory used is Dunn, W. N.'s theory which includes Effectiveness, Adequacy, Equity, Responsibility and Determination. The research methodology used is qualitative with a descriptive approach. Data collection techniques are observation, interviews and documentation. Based on research findings, it can be concluded that the quality of service from Command Center 112 is good and in accordance with regulations. However, there are several aspects that can still be improved to improve the quality of public services to the community, so that Command Center 112 service users are not disappointed with the services provided.